GOVERNING INTERFAITH SOLIDARITY: HOW YAKKUM INSTITUTIONALIZES CROSS-FAITH HUMANITARIAN ACTION IN THE 2022 CIANJUR EARTHQUAKE - Nurmiati, Dwi Rahayu; Rusyidi, Binahayati; Taftazani, Budi Muhammad; Chen, Yi-Yi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
This study analyzes how interfaith solidarity is negotiated and institutionalized within post-disaster humanitarian governance, focusing on the interaction between the Christian-based YAKKUM Emergency Unit (YEU) and Muslim communities affected by the 2022 Cianjur earthquake in Indonesia. Adopting a sociological approach to religion and humanitarian governance, this research employed a qualitative, in-depth case study design to examine the socially embedded processes of legitimacy, cooperation, and moral negotiation in a religiously homogeneous setting. Data were collected through in-depth interviews with 24 informants, participatory observation across multiple emergency and recovery sites, and analysis of institutional and policy documents. They were analyzed using thematic analysis supported by NVivo 12 Plus. The findings identify four interrelated dimensions that enabled constructive interfaith engagement: equality of status between humanitarian actors and affected communities, shared humanitarian goals grounded in collective moral commitment, intergroup cooperation enacted through participatory practices, and institutional and normative support from state agencies and religious authorities. These dimensions demonstrate that interfaith solidarity in disaster contexts is not a spontaneous moral response, but an institutionalized social practice embedded within local cultural values such as gotong royong and universal compassion. The study contributes to the literature by extending Intergroup Contact Theory into a socio-normative and institutional framework, highlighting the role of cultural legitimacy and governance structures in shaping interfaith relations during crises. Practically, the findings offer empirically grounded insights for strengthening inclusive humanitarian governance and for developing capacity-building frameworks for faith-based organizations operating across religious boundaries in plural societies. Abstrak Penelitian ini bertujuan untuk menganalisis bagaimana solidaritas lintas iman dinegosiasikan dan diinstitusionalisasikan dalam tata kelola kemanusiaan pascabencana, dengan fokus pada interaksi antara YAKKUM Emergency Unit (YEU) yang berbasis Kristen dan komunitas Muslim terdampak gempa Cianjur tahun 2022. Dengan menggunakan pendekatan sosiologis terhadap agama dan tata kelola kemanusiaan, penelitian ini menerapkan desain studi kasus intrinsik kualitatif untuk menelaah proses sosial yang terlekat pada pembentukan legitimasi, kerja sama, dan negosiasi moral dalam konteks masyarakat yang relatif homogen secara keagamaan. Data dikumpulkan melalui wawancara mendalam terhadap 24 informan, observasi partisipatif pada berbagai lokasi tanggap darurat dan pemulihan, serta analisis dokumen kelembagaan dan kebijakan, yang kemudian dianalisis menggunakan analisis tematik dengan bantuan NVivo 12 Plus. Temuan penelitian menunjukkan empat dimensi yang saling berkaitan dalam membentuk interaksi lintas iman yang konstruktif, yaitu kesetaraan status antara aktor kemanusiaan dan masyarakat terdampak, tujuan kemanusiaan bersama yang berlandaskan komitmen moral kolektif, kerja sama antarkelompok yang diwujudkan melalui praktik partisipatif, serta dukungan institusional dan normatif dari negara dan otoritas keagamaan. Keempat dimensi tersebut menunjukkan bahwa solidaritas lintas iman dalam konteks kebencanaan bukanlah respons moral yang spontan, melainkan praktik sosial yang terinstitusionalisasi dan berakar pada nilai-nilai budaya lokal seperti gotong royong dan welas asih universal. Secara teoretis, penelitian ini berkontribusi dengan memperluas Teori Kontak Antarkelompok ke dalam ranah sosio-normatif dan institusional, dengan menekankan peran legitimasi budaya dan struktur tata kelola dalam membentuk relasi lintas iman pada situasi krisis. Secara praktis, temuan ini memberikan dasar empiris bagi penguatan tata kelola kemanusiaan yang inklusif serta pengembangan kerangka penguatan kapasitas bagi organisasi kemanusiaan berbasis iman yang beroperasi lintas batas keagamaan dalam masyarakat plural.